Efektifitas Validasi Bea Perolehan Hak atas Tanah dan Bangunan terhadap Ketidaksesuaian Nilai Objek Pajak dalam Akta Jual Beli dengan Harga Sebenarnya - Dejan Gemelar Raja Guk-Guk; Isnaini Isnaini; M. Citra Ramadhan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to determine the effectiveness of the validation of Land and Building Rights Acquisition Duty (BPHTB) against tax object value discrepancies, the BPHTB validation process carried out by the Medan City Regional Revenue Service (BPPRD) and how to determine the Tax Object Principal Value (NPOP) in accordance with the actual value of the tax object. This type of research is a descriptive normative research. The effectiveness of BPHTB validation against the discrepancy in the value of tax objects is seen based on the BPHTB revenue data mentioned above, it is known that the number of targets and realization of BPHTB taxes seen from 2017 to 2019 is quite effective. The BPHTB validation process carried out by the Medan City BPPRD in general is quite satisfactory, plus currently the BPHTB SSPD validation process is carried out with an online system, so that the BPHTB SSPD validation process becomes easier and faster. How to determine the Principal Value of the Tax Object (NPOP) by determining the transaction value in the sale and purchase transaction. The use of the transaction value used as the basis for calculating BPHTB often creates problems. The difference in the transaction value agreed by the parties and stated in the deed with the transaction value used as the basis for calculating BPHTB according to BPPRD research, in this case there is uncertainty about which value is correct, so determining the NPOP in accordance with the actual value of the tax object becomes difficult. except by conducting field verification on the said BPHTB object.